(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2025)
Even with the act of birth, we, as human beings are “assigned” different” identities that differ from our wishes. The same identities that we are assigned at birth continue to be further moulded and shaped through the process of socialization. Even so, sometimes we even discredit or “give up” on those identities entirely. The focal point of this thesis is placed upon the human sexuality, culture, and society, and the ways the socio-cultural context influence the shaping of human sexuality. Hence, my efforts to hirghlight the enormous influence of the culture over the modelling of the human sexuality. In fact, the aim of this academic presentation is to discredit the traditional claims (that do not possess evidence of the claim) that sexual desire, i.e., sexuality as a whole, is treated as a kind of given or genetically predisposed occurrence (also referring to heterosexuality as the sole, healthy sexual desire). In the same notion, I intend to unveil the influence of the social and cultural factors in the shaping of the sexual behaviour, which are rather significant factors that have been greatly ignored throughout history. The sexual behaviours of people hold certain meanings – people use and express their sexuality in a variety of ways. To people, there is more to sexual activity than just biology. In that context, we shall consider culture as the rudimentary determinant in the process of the formation of human sexuality. In the light of such occurrences, the need for a more exact examination of the role of the culture in the shaping of human sexuality arises. Besides impacting the shape of human sexuality, culture is an inevitable influencer of the gender self-identification in time and space.